INDEX TUNABLE THIN FILM INTERFERENCE COATINGS - MURANO, ROBERT; SHERMAN, STEVEN; WU, MING; MA, EUGENE; PAYNE, ADAM; DOMASH, LAWRENCE; NEMCHUK, NIKOLAY; WAGNER, MATTHIAS (2002)
According to various embodiments and aspects of present invention, there is provided a dynamically tunable thin film interference coating including one or more layers with thermo-optically tunable refractive index. Tunable layers within thin film interference coatings enable a new family of thin film active devices for the filtering, control, modulation of light. Active thin film structures can be used directly or integrated into a variety of photonic subsystems to make tunable lasers, tunable add-drop filters for fiber optic telecommunications, tunable polarizers, tunable dispersion compensation filters, and many other devices. L'invention concerne un revêtement interférentiel à couches minces, accordable de manière dynamique, comprenant une ou plusieurs couches à indice de réfraction accordable par voie thermo-optique. Les couches accordables dans ces revêtements interférentiels à couches minces permettent de créer une nouvelle famille de dispositifs actifs à couches minces servant à filtrer, réguler, moduler la lumière. Ces structures à couches minces actives peuvent être utilisées directement ou intégrées dans une variété de sous-système photoniques pour permettre la production de lasers accordables, de filtres d'insertion-extraction accordables destinés aux télécommunications à fibres optiques, de polariseurs accordables, de filtres de compensation de dispersion accordables, ainsi qu'un grand nombre d'autres dispositifs.